Arabic Language Learning: An In-Depth Examination of Students' Challenges and Solutions - Setiadi, Fadlan Masykura; Khairunnisa (The Progress: Journal of Language and Ethnicity, 2023)
This study aimed to provide an extensive analysis of the challenges faced by students at the SD-IT Riyadhoturrohman, Mandailing Natal in the process of learning the Arabic language and proposes effective solutions to overcome these obstacles. Arabic is a language of rich cultural and historical significance, yet its complexity poses unique challenges for learners. By delving into the specific difficulties encountered by students, this research seeks to contribute valuable and effective insights to teachers, curriculum developers, and policymakers involved in Arabic language learning practices.